MODY2 diagnostic issues in adults - Irina V. Kononenko; Anastasiya A. Glibka; Natalya A. Zubkova; Alexander Y. Mayorov; Anatoly N. Tyulpakov; Olga M. Schmidt (Сахарный диабет)
Approximately 90% of all cases of diabetes mellitus in adults involve type 2 diabetes, while the prevalence of maturity-onset diabetes of the young (MODY) remains undetermined leading to inappropriate treatment regimens. One of the most common monogenic forms of diabetes is a disease caused by a mutation in the glucokinase gene, MODY2. Knowledge of the clinical features of the disease allows the selection of patients with a high risk of mutation in the glucokinase gene and verification of diagnosis for molecular genetic research. This paper reflects the clinical features of MODY2 and the difficulties of diagnosis in adults. Furthermore, it presents a clinical case of a patient with MODY2 demonstrating all the features of this type of diabetes. A family member with a mutation in the gene allows to predict the nature of carbohydrate metabolism disorders in first degree relatives. A targeted study of only one part of the glucokinase gene in molecular genetic research is sufficient to confirm the diagnosis in relatives.